(3GdJHQ GdeSHhc aj fUjMI Gdedhcs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s ((3eMeO Hf eMeO s)
(3ChdgG (B:s
(3GdMeO ddg Ydi CfYGeg hCaVGdg hHYO aEfg SCdfi HYV GdcHQGA GYde jG SdWGf GdYGde Ef Gddg JYGdi Ydjc fYe XGgQI hHGWfI Ydjc TcQgG s
(3BNQgG (B:s
(3hYLGjH GdfShGfi cd GdHdG efgf jCJi hGdhaGA efgf dG jCJi eOG GdCReGf Je GdcJGH hGdMeO ddg s
(3GdeNWhW JQLeg deNWhW fUjMI Gdedhc GdPi Cdag GdZRGdi HGdaGQSjI hCgOGg ddSdWGf eMeO Hf edcTGg GdSdLhbi SfI (B505s
(3HChdg Jedc SfI (B1077 (3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
Keywords: (3GdSjGSI hGdGLJeGYs